Prevalence of oral anticoagulation in atrial fibrillation - Bartholomay, Eduardo; Polli, Ismael; Borges, Anibal Pires; Kalil, Carlos; Arroque, André; Kohler, Ilmar; Danzmann, Luiz Cláudio (Clinics (São Paulo, Brazil), 2014)
Atrial fibrillation is the most common sustained arrhythmia and is associated with poor outcomes, including stroke. The ability of anticoagulation therapy to reduce the risk of stroke has been well established; however, the prevalence of anticoagulation therapy use in the Public Health System is unknown. The aim of this study is to evaluate both the prevalence of anticoagulation therapy among patients with atrial fibrillation and the indications for the treatment. In this cross-sectional study, we included consecutive patients who had atrial fibrillation documented by an electrocardiogram performed between September 2011 and March 2012 at a university hospital of the Public Health System. The variables analyzed included the risk of a thromboembolic event and/or bleeding, the use of antiplatelet or anticoagulation therapy, the location where the electrocardiogram report was initially reviewed and the specialty of the physician who initially reviewed it. We included 162 patients (mean age 68.9 years, 56% men). Hypertension (90.1%), heart failure (53.4%) and stroke (38.9%) were the most prevalent diseases found. Only 50.6% of the patients knew that they had atrial fibrillation. Regarding the use of therapy, only 37.6% of patients classified as high risk according to the CHADS2 scores and 35.5% according to the CHA2DS2VASc used oral anticoagulation. A presumptive diagnosis of heart failure and the fact that the electrocardiogram was evaluated by a cardiologist were the only independent predictors of the use of anticoagulants. Our study found a low prevalence of oral anticoagulation therapy among patients with atrial fibrillation and an indication for stroke prophylaxis for the use of this therapy, including among those with high CHADS2 and CHA2DS2VASc scores.